Behavior of Expansive Clay of Ngawi Region (East Java) Under Water Content Variation - Agus Setyo Muntohar (Civil Engineering Dimension, 2009)
The authors have prepared a significant investigation in swelling behavior of expansive clay. The lateral swelling potential obtained from modified oedometer test was especially interesting. Discussant used the term of swelling potential to represent both strain and swelling pressure. The effect of three different initial water contents, which is 20%, 25%, and 30%, on swelling potential has been studied. The specimens were prepared at similar densities. The lateral swelling potential has been measured from the installed strain gauges. However, installation of the strain gauges and procedure of the test were not clearly informed. Two discussions will be presented as follows.